The Future of Sino-Russian Relations - Shokhrukh Ashrafi (Department of Political Science - Universitas Sains Al-Qur’an, 2019)
Today China and Russia declare the strategic partnership between each other and confidently assure each other in the consistency of their actions and commitment to the mutual growth and win-win cooperation. However, if China’s commitment is visible and evident, same cannot be said about Russia: it has been stagnating for over a decade while China’s fast growing economy has been conquering the markets throughout the world; Russia has been spoiling its relations with all European states, that are obviously, at now, an economic and political power, and even with the former allies (Ukraine, Armenia, Belarus); and Russia is not only unable to solve the domestic problems but even worsening them, considering the racism, xenophobia and poverty problems.